World without weight : perspectives on an alien mind - Povinelli, Daniel J. (Oxford : Oxford University Press, 2012)
In every domain of reasoning humans deploy a wide range of intuitive 'theories' about how the world works. So are we alone in trying to make sense of the world by postulating theoretical entities to explain how the world works, or do we share this ability with other species? This is the focus of Povinelli's book.
Includes bibliographical references and index.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 21, 2012).
Keywords: Cognition